Combined Effects of Environmental Drivers on Marine Trophic Groups – A Systematic Model Comparison - Ehrnsten, Eva; Bauer, Barbara; Gustafsson, Bo G. (Frontiers in Marine Science, 2019)
The responses of food webs to simultaneous changes in several environmental drivers are still poorly understood. As a contribution to filling this knowledge gap, we investigated the major pathways through which two interlinked environmental drivers, eutrophication and climate, affect the biomass and community composition of fish and benthic macrofauna. For this aim, we conducted a systematic sensitivity analysis using two models simulating the dynamics of benthic and pelagic food webs in the Baltic Sea. We varied environmental forcing representing primary productivity, oxygen conditions and water temperature in all possible combinations, over a range representative of expected changes during the 21st century. Both models indicated that increased primary productivity leads to biomass increase in all parts of the system, however counteracted by expanding hypoxia. Effects of temperature were complex, but generally small compared to the other drivers. Similarities across models give confidence in the main results, but we also found differences due to different representations of the food web in the two models. While both models predicted a shift in benthic community composition towards an increased abundance of Limecola (Macoma) balthica with increasing productivity, the effects on deposit-feeding and predatory benthic groups depended on the presence of fish predators in the model. The model results indicate that nutrient loads are a stronger driver of change for ecosystem functions in the Baltic Sea than climate change, but it is important to consider the combined effects of these drivers for proper management of the marine environment.